Designing Digital Combination Keys on Safes - Kunto Wibowo; Bambang Harianto; Moohammad Karjadi (International Journal Labs, 2022)
A digital combination lock is a key that works electronically and only people who know the code can open it and close it. By doing several combinations consisting of 4 digits, namely by pressing the numbers 0 to 9 on the keypad keys. The digital combination lock on the safe consists of a krndali encoder, decoder, comperator, timer and shif register, also consists of a dc motor that serves to open and pop the safe door. The results of the trials that the safe door conducted when closing and opening it can be set using a potentiote with a lap time of between 1 to 5 seconds.